2016
DOI: 10.3389/fimmu.2016.00515
|View full text |Cite
|
Sign up to set email alerts
|

The A Allele of the Single-Nucleotide Polymorphism rs630923 Creates a Binding Site for MEF2C Resulting in Reduced CXCR5 Promoter Activity in B-Cell Lymphoblastic Cell Lines

Abstract: Chemokine receptor CXCR5 is highly expressed in B-cells and under normal conditions is involved in their migration to specific areas of secondary lymphoid organs. B-cells are known to play an important role in various autoimmune diseases including multiple sclerosis (MS) where areas of demyelinating lesions attract B-cells by overexpressing CXCL13, the CXCR5 ligand. In this study, we aimed to determine the functional significance of single-nucleotide polymorphism rs630923 (A/C), which is located in cxcr5 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…However, they did not observe any difference between alleles [35]. Two years later, Mitkin et al also employed a luciferase assay to analyze the CXCR5 gene promoter activity influenced by rs630923 and observed that the minor allele (A) created a MEF2C transcription factor binding site that involved a decreased transcriptional activity in Raji cells [36]. Since rs630923 is in low LD with rs10892307 (r 2 = 0.039), the variant that best capture one of the associations in our population for the CXCR5 region, we believe that the functional effect described in Raji cells [36] must be related to other of the MS association signals of the locus.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not observe any difference between alleles [35]. Two years later, Mitkin et al also employed a luciferase assay to analyze the CXCR5 gene promoter activity influenced by rs630923 and observed that the minor allele (A) created a MEF2C transcription factor binding site that involved a decreased transcriptional activity in Raji cells [36]. Since rs630923 is in low LD with rs10892307 (r 2 = 0.039), the variant that best capture one of the associations in our population for the CXCR5 region, we believe that the functional effect described in Raji cells [36] must be related to other of the MS association signals of the locus.…”
Section: Discussionmentioning
confidence: 99%
“…All PCR products were verified by sequencing; sequences of PCR primers are represented in Table S1 . Isolation of nuclear extracts, formation and immunoprecipitation of DNA-protein complexes, and the evaluation of bound DNA probes by RT-PCR were performed as described [ 72 ]. Rabbit polyclonal anti-CREB1 antibody (ab31387, Abcam, Cambridge, UK) was precipitated with pre-blocked magnetic beads (Thermo Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It also controls cardiac morphogenesis and myogenesis, and is likewise involved in vascular development. Enhances transcriptional activation mediated by SOX18 [16,17]. The next place in the table was placed by the TADA3 gene.…”
Section: Discussionmentioning
confidence: 99%